La traiettoria della Sapienza dall’AT a Giovanni, al NT e sviluppi ulteriori - Niccacci, Alviero (Liber Annuus, 2013)
Abstract This paper presents firstly a synthesis of several preceding studies of the author on the trajectory of Wisdom in the OT; from Prov 8 to Job 28, Sir 1, 24 and 51, Bar 3:9-4:4 and to Wis 9 (§ 1). Then it considers apocryphal texts regarding God appearing as a man (§ 2) and the gnostic myth of Wisdom who comes among men but is not accepted and goes back to heaven (§ 3); Jesus as Teacher of wisdom and personified Wisdom in the NT (§ 4), paying special attention to the Gospel of John on Jesus as the incarnate Word become flesh, dwelling among men and revealing the Father (§ 5), and also to the Letters of Paul and the rest of the NT (§ 6); and theological developments in the theme of Wisdom in the Church Fathers, medieval writers and modern authors (§ 7). Finally, the paper provides some concluding remarks by outlining three forms of God’s incarnation given to men, i.e., Creation, Holy Scripture and Eucharist.